OPTIMALISASI MANAJEMEN PEMBIAYAAN PENDIDIKAN BERBASIS PRIORITAS ANGGARAN DALAM MENDUKUNG MUTU PENDIDIKAN DASAR: STUDI KASUS DI SD NEGERI CIKANDANG 01 KABUPATEN BREBES - Julaiha; Lily Karati; Sutrisno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of educational financial management in supporting the improvement of educational quality at SD Negeri Cikandang 01. The study employed a qualitative approach with a single-case study design. Research participants consisted of the school principal, the school treasurer, two teachers, and the chairperson of the school committee, selected through purposive sampling. Data were collected through in-depth interviews, non-participant observation, and document analysis of the School Activity and Budget Plan (RKAS) for the 2026 fiscal year. Data analysis was conducted using an interactive model involving data reduction, thematic categorization, data display, and conclusion drawing, with validity ensured through source and technique triangulation. The findings reveal that the school remains highly dependent on Regular School Operational Assistance Funds (BOSP), amounting to IDR 135,780,000, with budget allocations predominantly directed toward routine operational needs rather than teacher capacity development. Under these fiscal constraints, the school implemented an adaptive fiscal prioritization strategy through the optimization of Teacher Working Group forums, continuous academic supervision, internal reflective discussions, and the utilization of free online professional development programs. This study concludes that the effectiveness of educational financial management in resource-constrained primary schools is determined more by strategic budget prioritization, managerial creativity of school leaders, and internal collaboration than by the nominal amount of available funding. The findings propose a conceptual model of efficiency- and collaboration-based financial optimization as a strategic alternative for public primary schools operating under limited fiscal capacity.